Antiplasmodial Activity of Stigmastane Steroids from Dryobalanops oblongifolia Stem Bark - Indriani, .- (Penerbit Water de Gruyter GmbH, 2020)
Three stigmastane steroids: 6-hydroxystigmast-4-en-3-one (1), stigmast-4-en-3-one (2), and 3-hydroxystigmast-5-en-7-one (3) were successfully isolated from the acetone extract of Dryobalanps oblongifolia stem bark. The structural determination of isolated compounds was carried out on the basis of data analysis of NMR and MS spectra. In order to identify the antiplasmodial activity, the isolated compound was put to test against Plasmodium falciparum 3D7. Antiplasmodial activity of the isolated compounds showed that the IC50 values of 6-hydroxystigmast-4-en-3-one were 37.29 μg/mL while the IC50 values of stigmast-4-en-3-one were 43.54 μg/mL and the IC50 values of 3-hydroxystigmast-5-en-7-one were 13.34 μg/mL (chloroquine phosphate was used as a positive control, IC50 0.006 μg/mL). Judging from the results, the isolated compounds were proven to demonstrate mediocre antiplasmodial activity. Compound (3) indicated a better antimalarial activity than compound (1) and (2), even though there was no satisfactory activity that indicated its ability to combat chloroquine. Therefore, it might not be developed as an antimalarial drug.